Healing Social WithdrawalKyudo – The Art of Losing? - Olejarz, Sylwia Maria (Current Problems of Psychiatry, 2010)
The primary aim of my investigations is to present to broader circle of readers how people can make a great “therapeutic use” from the means available in the realm of one’s own culture.